Secondhand bride - Miller, Linda Lael (Miller, Linda Lael. McKettricks, 2022)
"The third installment in the New York Times bestselling McKettrick Cowboys series follows the youngest McKettrick brother as he and his estranged love cross paths after discovering he must marry in order to inherit the family ranch"--Amazon.